ON THE DISSEMINATION OF ACUPUNCTURE TO EUROPE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Acupuncture, in conjunction with moxibustion and the use of medicinal herbs, was developed in Ancient China, and is part of the Traditional Chinese Medicine. These practices were subsequently disseminated in Japan, and their further development gave rise to the Traditional Japanese Medicine. After the 17th century AD, these medical practices were disseminated in the West, mainly through the groundbreaking work of scientists and doctors, Willem Ten Rhijne and Engelbert Kaempfer. Central to this process was the existence of the Dutch Trading Post in Deshima Island, in the Bay of Nagasaki, which constituted the sole point of contact between Japan and the West for centuries. Owing to individual initiative and an established tradition of cultural and scientific exchange, at Deshima, acupuncture and Japanese medicine became known in Europe, providing the impetus for further cultural and scientific exchange.